2006
DOI: 10.1159/000089207
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Short-Time Killing Activity of Povidone-Iodine (Isodine<sup>®</sup> Gargle) in the Presence of Oral Organic Matter

Abstract: In order to estimate the clinical efficacy of a povidone-iodine oral antiseptic (PVP-I) on oral bacterial infectious diseases, we studied the effect of oral organic matter on the in vitro killing activity of PVP-I. In addition, we compared the in vitro short-time killing activity of PVP-I with those of other oral antiseptics using mouth-washing and gargling samples collected from healthy volunteers. When any of the mouth-washing and gargling samples was used, the standard (0.23–0.47%) or lower concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
4
16
1
Order By: Relevance
“…This result was also supported by many reports which indicated that the efficacy of PVP-I declined when organic matter (e.g. blood, fish mucus, amino acids, or simple aromatic compounds) was present Yoneyama et al, 2006). Similar results also had been observed in seawater that the content of molecular iodine reduced within hours when added to seawater (Truesdale, Luther & Canosa-Masb, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…This result was also supported by many reports which indicated that the efficacy of PVP-I declined when organic matter (e.g. blood, fish mucus, amino acids, or simple aromatic compounds) was present Yoneyama et al, 2006). Similar results also had been observed in seawater that the content of molecular iodine reduced within hours when added to seawater (Truesdale, Luther & Canosa-Masb, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…Data concerning the penetration of antiseptic agents into these vital tissues is scarce and the real concentrations during application under clinical conditions can only be estimated. Studies used different concentrations ranging from 0.1 % to 10 % [10-12], but no mandatory recommendations are given in literature so far. Laboratory conditions cannot be directly transferred to the situation of the bacterial biofilm in periodontal pockets in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Antiseptic mouth rinse solutions are used in many clinical situations for different therapeutic and prophylactic purposes [11, 12]. Many of those are recommended for homecare practice [11].…”
Section: Introductionmentioning
confidence: 99%